Vitamin D intoxication in patients with cystic fibrosis: report of a single-center cohort - Thomas Planté-Bordeneuve (Nature Portfolio, 2021)
Abstract Vitamin D toxicity is associated with accidental overdoses due to manufacturing or intake errors and its secondary hypercalcemia can result in severe morbidity. Although patients with cystic fibrosis are potentially at increased risk for this intoxication as prescription of vitamin D preparations is a common practice in this population, the frequency of such events is currently unknown. We performed a retrospective analysis of all the files of cystic fibrosis patients followed at the Cliniques universitaires Saint-Luc over a 10-year period, recording 25(OH)- and 1,25(OH)2vitamin D levels as well as demographic data, lung function tests, Pseudomonas aeruginosa infection and results from pharmacological analysis of magistral liposoluble vitamins preparations. A total of 244 patients were included in the study. 13 patients (5%) had serum vitamin D levels corresponding to vitamin D overdose. Patients who had experienced an overdose were more likely to be F508del homozygous or suffer from exocrine pancreatic insufficiency. 2 patients developed significant hypercalcemia necessitating monitoring and hospitalization. Errors in the preparation of magistral liposoluble vitamin pills were identified in several intoxicated patients. Retrospective assessment of the dosing errors with the local pharmacists showed that trituration and dosing errors were their most frequent causes.